Improving students’ metacognitive skills through science learning by ıntegrating PQ4R and TPS strategies at a senior high school in parepare, ındonesia - Setıawatı, Henny; Corebıma, Aloysius Duran (Journal of Turkish Science Education, 2018)
Metacognitive skills can be developed through the implementation of appropriate learning strategy. This research of pretest-posttest nonequivalent control group design was designed to compare the effects of PQ4R, TPS, PQ4R-TPS, and conventional learning on the metacognitive skills of senior high school students class X in the first semester of 2013 in Parepare, Indonesia. The research samples consisted of 240 students, selected using random sampling technique. The metacognitive skills were measured by an essay test developed by the researchers, validated by experts, and empirically validated before the instrument was used, by trying out the instruments at 40 students of class XI. The research findings show that PQ4R-TPS learning strategy is significantly more potential in empowering students’ metacognitive skills compared to the other learning. PQ4R-TPS learning strategy needs to be implemented, accustomed to, and continuously trained to the students in order to improve their metacognitive skills.